The mechanism of oleic acid deoxygenation to green diesel hydrocarbon using porous aluminosilicate catalysts - Nugraha, Reva Edra; Purnomo, Hari; Aziz, Abdul; Holilah, Holilah; Bahruji, Hasliza; Asikin-Mijan, Nurul; Suprapto, Suprapto; Taufiq-Yap, Yun Hin; Abdul Jalil, Aishah; Hartati, Hartati; Prasetyoko, Didik (Elsevier, 2024)
The role of mesoporous solid acid aluminosilicate in the oleic acid deoxygenation was elucidated using ZSM-5 and Al-MCM-41 impregnated with Ni. The mesoporous supports were synthesized using a similar initial Si/Al ratio but employing different templates to vary the mesopores. ZSM-5_T produced interparticle mesopores when using TPAOH (tetrapropylammonium hydroxide) as a template. Meanwhile, ZSM-5_S with a well-defined intraparticle mesoporous channel was formed using a silicalite template. Al-MCM-41 synthesized without a template produced one-dimensional highly ordered mesoporous channels. The arrangement of mesoporosity in aluminosilicate determined the mechanistic pathway of oleic acid conversion into hydrocarbon. Oleic acid underwent primary thermal cracking into carboxylic acid before progressing into the subsequent decarbonylation reaction. The diesel hydrocarbon yield was enhanced following the order of Al-MCM-41>ZSM-5_S>ZSM-5_T>blank reaction. Large intraparticle mesoporosity produced long-chain carboxylic acid from catalytic cracking of oleic acid, which was subsequently deoxygenated into long-chain hydrocarbons.